Awareness and utilization of contraceptives among males of reproductive age, Jos North, Plateau state, Nigeria - Osagie, Ize A.; Envuladu, Esther A.; Thilza, Solomon; Amina, Mohammed; Nnanna, Jemie U.; Rijam, Vasita N.; Gloria, Joseph E. (International Journal Of Community Medicine And Public Health, 2020)
Background: Modern contraceptives are relevant interventions in the reduction of maternal and child morbidity and mortality. Its uptake by females of reproductive age has been found to be influenced by male partners’ awareness and utilization. This study aimed to determine the awareness of contraceptives, utilization prevalence and sociodemographic predictors for use among males of reproductive age in Jos North. Methods: A cross sectional study involving 406 males of reproductive age who were selected by multistage sampling technique. Data was collected using an interviewer-administered semi-structure questionnaire and analysed using SPSS version 23.0. At 95% confidence interval, a p value of <0.05 was considered statistically significant. Results: There was a high awareness prevalence of contraceptives 378 (93.1%). However, the prevalence of current contraceptive use with partners was low 160 (42.3%). Respondents who were single were more likely to use contraceptives than those who were married or separated (OR 1.8; 95% CI 1.109-2.251). Those between the ages of 35-44 years also had a higher likelihood of using modern contraceptives than younger men (OR 2; 95% CI 0.410-2.436). Education, occupation and family size had no statistically significant association with contraceptive use among respondents. Conclusions: Despite the high awareness of modern contraceptives among respondents in this study, utilization with partners was low. Predictors of utilization were being single and being in the third decade of life. This could impact on increased risk for both maternal and child mortality. Male targeted contraceptive education is necessary at community levels to improve uptake.